Self-Generated Hypoxia Leads to Oxidative Stress and Massive Death in Ustilago maydis Populations under Extreme Starvation and Oxygen-Limited Conditions - Petkovic, Jelena (J Fungi (Basel), 2021)
Ustilago maydis and Saccharomyces cerevisiae differ considerably in their response to water-transfer treatments. When stationary phase cells were transferred to pure water and incubated under limited supply of oxygen, the U. maydis cells suffered a catastrophic loss of viability while the S. cerevisiae population was virtually unaffected by the treatment. The major factor underlying the death of the U. maydis cells under those conditions was an oxygen-consuming cellular activity that generated a hypoxic environment, thereby inducing oxidative stress and accumulation of reactive oxygen species, which resulted in lethality. Importantly, a small residue of U. maydis cells that did survive was able to resume growth and repopulate up to the initial culture density when sufficient aeration was restored. The regrowth was dependent on the cellular factors (Adr1, Did4, Kel1, and Tbp1), previously identified as required for repopulation, after killing with hydrogen peroxide. Surprisingly, the survivors were also able to resume growth under apparently hypoxic conditions, indicating that these remnant cells likely switched to a fermentative mode of growth. We discuss the findings in terms of their possible relevance to the eco-evolutionary adaptation of U. maydis to risky environments.